PERAN AKTIF BERORGANISASI TERHADAP PERKEMBANGAN KARIR DAN JIWA KEPEMIMPINAN DI KALANGAN MAHASISWA (Studi Kualitatif di Kampus Institut Agama Islam Pemalang) - Husna Dianti Putri (Promis, 2025)
The aim of this research is to determine students' attitudes towards organizational activities in career adaptation in the local area. The benefits of research include theoretical benefits and practical benefits. The method used in this research is to conduct a literature review and conduct an observational study based on previous research. Through library research, researchers examine and collect data through various sources and readings that support and are relevant to the research. The results of this research focus the discussion on the importance of organizational experience in training soft skills for students. All respondents answered that organizational experience in training soft skills for students is very important, because organizing can build soft skills that we have not mastered so far, so that we can master them more. master its development, and has many benefits that can be applied on campus and in society. Apart from that, students who are active in organizations are generally more likely to get a job even though they are still active in college.